Uso de geotecnologias em modelos de estimativa de produtividade de soja no estado do Paraná - Richetti, Jonathan (2015)
In order to propose an objective methodology to estimate soybean crop yield in Western Paraná, the present research explored three different models for estimating soybean crop yield. One agrometeorological model (FAO model), presented four estimates based on agrometeorological data from remote sensing (ECMWF) and data collected in loco; one spectral model (GLO-PEM2 model), which used data from a MODIS sensor to estimate soybean crop yield in the state; and one agro-spectral model (CASA model), which presented two estimates, based in agrometeorological data and MODIS sensor data. The present work determined water balance and real evapotranspiration through two methods (BHTM and BHFAO). The soil data was collected from EMBRAPA, the culture s was from FAO, the dates of planting and harvest were determined by Becker (2013) and the agrometeological data was obtained from ECMWF. The spectral data utilized was provided by the MODIS sensor, namely Terra and Aqua platforms. The GLO-PEM2 proved to be rather weak and requires further investigation; the CASA and FAO models presented good results, lightly overestimating productivity, while compared to the official data. Therefore, this research presented an objective metholodogy for estimating soybean crop yeild in the state of Paraná.